Effects of increasing crystalline amino acids in sorghum- or corn-based diets on nursery pig growth performance - Jordan, Kyle E.; Nemechek, Jeremiah E.; Goncalves, Marcio Antonio Dornelles; Goodband, Robert D.; Tokach, Michael D.; Dritz, Steven S.; DeRouchey, Joel M.; Woodworth, Jason C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2015)
A total of 300 pigs (PIC 1050; initially 23.3 lb BW) were used in a 21-d study to compare the effects of increasing crystalline amino acids in sorghum- and corn-based diets on nursery pig growth performance. Treatments with 5 pigs per pen and 10 pens per treatment were arranged in a 2 × 3 factorial with main effects of grain source (sorghum vs. corn) and crystalline amino acid supplementation (low, medium, or high). Amino acid ratios to lysine as well as standardized ileal digestibility coefficients used were set by NRC (20123). Because replacing increasing amounts of soybean meal with crystalline amino acids changes the NE of the diet, all diets were formulated to the same Lys:NE ratio. The lysine concentration in the diets was formulated at 95% of the pig’s estimated requirement to ensure that the other amino acids, on a ratio to lysine, would not be underestimated. The grain sources and soybean meal were analyzed for amino acid profile and diets formulated from these concentrations. The low amino acid fortification contained L-lysine HCl and DL-methionine. The medium amino acid fortification contained L-lysine HCl, DL-methionine, and L-threonine, and the high amino acid fortification contained L-lysine HCl, DL-methionine, L-threonine, and L-valine. Overall, no main or interactive effects (P > 0.05) of grain source or added amino acids were detected for any response criteria. This suggests that balancing to the third, fourth, or fifth limiting amino acids is possible in both sorghum- and corn-based diets with the use of crystalline amino acids without detrimental effects on growth performance.
Swine Industry Day, 2014 is known as Swine Day, 2014
Keywords: Corn; Crystalline amino acid; Nursery pig; Sorghum